2021
DOI: 10.1186/s12939-021-01514-2
|View full text |Cite
|
Sign up to set email alerts
|

Cultural determinants of health for Aboriginal and Torres Strait Islander people – a narrative overview of reviews

Abstract: Introduction The cultural determinants of health centre an Indigenous definition of health, and have been linked to positive health and wellbeing outcomes. There is growing evidence for the importance of the cultural determinants of health; however, to date, no high-level overview of the evidence-base has been provided. Synthesising existing literature on cultural determinants of health for Aboriginal peoples in a single manuscript will highlight what we know, and what needs to be explored in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…It is within the family and the community where Indigenous culture, knowledge and language is transmitted, positive cultural identity forms, and where one can seek out support in a crisis [103]. However, in many Indigenous contexts, family and community environments have been severely damaged with colonization [13,104]. Hence why community engagement outcomes consistently point to a need to move beyond the individual to support family and community strengths [49].…”
Section: Discussionmentioning
confidence: 99%
“…It is within the family and the community where Indigenous culture, knowledge and language is transmitted, positive cultural identity forms, and where one can seek out support in a crisis [103]. However, in many Indigenous contexts, family and community environments have been severely damaged with colonization [13,104]. Hence why community engagement outcomes consistently point to a need to move beyond the individual to support family and community strengths [49].…”
Section: Discussionmentioning
confidence: 99%
“…Participants are provided with a gateway into te ao Māori and a safe space to learn about and explore their cultural identity in relation to the teachings of tikanga Māori. Studies have shown that cultural practices have an inextricable link to health and wellbeing, with evidence that a secure cultural identity enhances mental wellbeing and alleviates symptoms of depression 21–25 . This shows that securing cultural identity is an important determinant of health from an indigenous perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cultural practices have an inextricable link to health and wellbeing, with evidence that a secure cultural identity enhances mental wellbeing and alleviates symptoms of depression. [21][22][23][24][25] This shows that securing cultural identity is an important determinant of health from an indigenous perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural determinants : Verbunt et al (2021) examined cultural DOH among Aboriginal and Torres Strait Islander people in Australia. They identified four factors that have positive impacts on the health of indigenous populations.…”
Section: The “Further Upstream and Farther Downstream” Frameworkmentioning
confidence: 99%